An ester-thiophene-hexylthiophene copolymer and its preparation method and application
By using ester-hexylthiophene copolymer as the hole transport layer material in perovskite solar cells and introducing 3-ester-thiophene chain segments, the problem of low variable output voltage in the prior art is solved, and the energy conversion efficiency is improved.
Patent Information
- Application Number
- CN202411519598.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing perovskite solar cells have high highest occupancy of molecular orbital (HOMO) energy level of poly(3-hexylthiophene) (P3HT), resulting in a low variable output voltage, limiting the improvement of energy conversion efficiency.
Ester thiophene-hexylthiophene copolymer is used as the hole transport layer material. By introducing 3-ester thiophene segments into the copolymer, the variable output voltage is improved, thereby improving the energy conversion efficiency.
While maintaining a high short-circuit current density and fill factor, the variable output voltage is improved, which significantly improves the energy conversion efficiency of perovskite solar cells.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thiophene copolymers, and in particular to an esterthiophene-hexylthiophene copolymer and a preparation method and application thereof. Background Art
[0002] Among the many new types of batteries that utilize solar energy, perovskite solar cells have stood out in the past two years due to their advantages such as low raw material prices, simple production process, ability to be prepared on flexible substrates, and large-area preparation by coating, printing, etc.
[0003] Energy conversion efficiency is one of the important indicators to measure the quality of perovskite solar cells, and the hole transport layer has an important influence on the energy conversion efficiency of perovskite solar cells. Poly(3-hexylthiophene) (P3HT) is often used to prepare hole transport layer materials due to its excellent carrier mobility and low-cost manufacturing. However, P3HT has a high highest occupied molecular orbital (HOMO) energy level (-4.90 eV), which leads to that solar cells based on P3HT often have a low variable output circuit voltage, limiting the further improvement of its energy conversion efficiency. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects and shortcomings of the prior art and to provide an ester-thiophene-hexylthiophene copolymer that can increase the variable output voltage while maintaining a relatively high short-circuit current density and fill factor, thereby effectively improving the energy conversion efficiency.
[0005] The object of the present invention is to provide an esterthiophene-hexylthiophene copolymer, wherein the esterthiophene-hexylthiophene copolymer is a copolymer of 3-hexylthiophene and esterthiophene, wherein the esterthiophene is selected from at least one of 3-(2-acetoxyethyl)thiophene and 3-(2-acetoxymethyl)thiophene, and wherein the molar percentage of the esterthiophene segment in the esterthiophene-hexylthiophene copolymer segment is 2.9% to 20%.
[0006] In some embodiments of the present invention, the molar percentage of the ester-thiophene chain segment to the ester-thiophene-hexylthiophene copolymer chain segment is 2.9% to 9% or 16% to 20%.
[0007] In some embodiments of the present invention, the number average molecular weight of the ester thiophene-hexyl thiophene copolymer is 4.7-13.8 KDa.
[0008] In some embodiments of the present invention, the esterthiophene-hexylthiophene copolymer is a random copolymer.
[0009] In some embodiments of the present invention, the structure of the ester thiophene-hexyl thiophene copolymer is as shown in formula (I) or formula (II):
[0010]
[0011] Formula (I) Formula (II)
[0012] The molar percentage of the ester-thiophene chain segment to the ester-thiophene-hexylthiophene copolymer chain segment is 2.9% to 20%.
[0013] In some embodiments of the present invention, the structure of the ester thiophene-hexyl thiophene copolymer is as shown in formula (I) or formula (II):
[0014]
[0015] Formula (I) Formula (II)
[0016] The molar percentage of the ester-thiophene chain segment in the ester-thiophene-hexylthiophene copolymer chain segment is 2.9% to 9% or 16% to 20%.
[0017] In some embodiments of the present invention, the HT value of the esterthiophene-hexylthiophene copolymer is ≥80%, and the PDI is ≤2.5.
[0018] Another object of the present invention is to provide a method for preparing an ester-thiophene-hexylthiophene copolymer, comprising the following steps:
[0019] Under the catalysis of pyridine carboxaldehyde palladium catalyst, the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene react to obtain the ester thiophene-hexylthiophene copolymer;
[0020] The bromine-substituted ester-based thiophene is selected from at least one of 2-bromo-3-(2-acetoxyethyl)thiophene and 2-bromo-3-(2-acetoxymethyl)thiophene.
[0021] In some embodiments of the present invention, the pyridine carboxaldehyde palladium catalyst is selected from a dipyridine carboxaldehyde palladium catalyst, and the structure of the dipyridine carboxaldehyde palladium catalyst is shown below:
[0022] .
[0023] In some embodiments of the present invention, the molar ratio of the bromine-substituted ester thiophene to 2-bromo-3-hexylthiophene is 3-25:75-97.
[0024] In some embodiments of the present invention, the ratio of the total mole of the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene to the mole of the palladium catalyst is 1:0.001-0.01.
[0025] In some embodiments of the present invention, the reaction temperature is 80-120° C. and the reaction time is 12-36 hours.
[0026] In some embodiments of the present invention, the reaction further contains an inorganic base, an organic acid and a solvent.
[0027] In some embodiments of the present invention, the inorganic base includes at least one of potassium carbonate and sodium carbonate.
[0028] In some embodiments of the present invention, the organic acid includes at least one of pivalic acid and caproic acid.
[0029] In some embodiments of the present invention, the solvent includes N,N-dimethylacetamide.
[0030] In some embodiments of the present invention, the ratio of the total mole of the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene to the mole of the inorganic base is 1-1.5:1-1.5.
[0031] In some embodiments of the present invention, the ratio of the total mole of the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene to the mole of the organic acid is 2.5-4.5:1.
[0032] In some embodiments of the present invention, after the reaction is completed, a purification step is further included.
[0033] Another object of the present invention is to provide the use of the ester-thiophene-hexylthiophene copolymer or the ester-thiophene-hexylthiophene copolymer prepared by the preparation method of the ester-thiophene-hexylthiophene copolymer in the preparation of perovskite solar cells.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The molecular structure of the esterthiophene-hexylthiophene copolymer provided by the present invention contains a 3-esterthiophene segment, which can effectively increase the voltage of the variable output circuit, thereby effectively improving the energy conversion efficiency of the perovskite solar cell.
[0036] (2) The ester-thiophene-hexylthiophene copolymer provided by the present invention has an irregular structure, high regularity and high molecular weight, and can effectively inhibit the aggregation of the ester-thiophene-hexylthiophene copolymer and improve the solubility and processability of the material in the solvent.
[0037] (3) The molecular chain of the ester-thiophene-hexylthiophene copolymer provided by the present invention contains a long chain and an ester bond structure, which can improve the solubility of the ester-thiophene-hexylthiophene copolymer in chlorobenzene and / or dichlorobenzene. The ester-thiophene-hexylthiophene copolymer provided by the present invention has broad application prospects in the fields of solar cells, organic transistors, electrochromic devices, chemical sensors, electromagnetic shielding materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the H NMR spectrum of the esterthiophene-hexylthiophene copolymer L1 provided in Example 1.
[0039] Figure 2 This is the H NMR spectrum of the esterthiophene-hexylthiophene copolymer L2 provided in Example 2.
[0040] Figure 3 This is the H NMR spectrum of the esterthiophene-hexylthiophene copolymer L3 provided in Example 3.
[0041] Figure 4 This is the H NMR spectrum of the esterthiophene-hexylthiophene copolymer L4 provided in Example 4.
[0042] Figure 5 This is the H NMR spectrum of the esterthiophene-hexylthiophene copolymer L5 provided in Example 5.
[0043] Figure 6 This is the H NMR spectrum of the esterthiophene-hexylthiophene copolymer L6 provided in Example 6. DETAILED DESCRIPTION
[0044] The following will clearly and completely describe the concept of the present invention and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can all be reagents and materials obtained from commercial channels.
[0045] In the following examples and comparative examples, the ester thiophene segment content in the ester thiophene-hexyl thiophene copolymer was measured by nuclear magnetic resonance, the ester thiophene-hexyl thiophene copolymer was dissolved in deuterated chloroform, TMS was used as the internal standard, and the measurement temperature was 25°C. The molecular weight or degree of polymerization of the ester thiophene-hexyl thiophene copolymer was measured by gel permeation chromatography (GPC) with THF mobile phase. Among them, HT and HT values represent isotacticity, and PDI represents molecular weight distribution index;
[0046] The structural formula of 2-bromo-3-(2-acetoxymethyl)thiophene is as follows:
[0047] ;
[0048] The structural formula of 2-bromo-3-(2-acetoxyethyl)thiophene is as follows:
[0049] .
[0050] Example 1
[0051] This embodiment provides an ester-thiophene-hexylthiophene copolymer L1, and the synthesis method thereof is as follows:
[0052] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.015mmol), 2-bromo-3-hexylthiophene (0.485mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L1 was obtained by precipitation in methanol. The yield was 77%, the HT value was 88%, the PDI was 2.1, the number average molecular weight Mn was 13.4KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 2.9%, that is, the copolymerization degree was 2.9mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L1 are as follows:
[0053]
[0054] Among them, x=2.9mmol%, y=97.1mmol%.
[0055] Example 2
[0056] This embodiment provides an ester-thiophene-hexylthiophene copolymer L2, and the synthesis method thereof is as follows:
[0057] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.025mmol), 2-bromo-3-hexylthiophene (0.475mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L2 was obtained by precipitation in methanol. The yield was 73%, the HT value was 85%, the PDI was 2.2, the number average molecular weight Mn was 13.8KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 4.3%, that is, the copolymerization degree was 4.3mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L2 are as follows:
[0058]
[0059] Among them, x=4.3mmol%, y=95.7mmol%.
[0060] Example 3
[0061] This embodiment provides an ester-thiophene-hexylthiophene copolymer L3, and the synthesis method thereof is as follows:
[0062] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.05mmol), 2-bromo-3-hexylthiophene (0.45mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L3 was obtained by precipitation in methanol. The yield was 68%, the HT value was 85%, the PDI was 1.8, the number average molecular weight Mn was 5.9KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 9%, that is, the copolymerization degree was 9mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L3 are as follows:
[0063]
[0064] Among them, x=9mmol%, y=91mmol%.
[0065] Example 4
[0066] This embodiment provides an ester-thiophene-hexylthiophene copolymer L4, and the synthesis method thereof is as follows:
[0067] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.075mmol), 2-bromo-3-hexylthiophene (0.425mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L4 was obtained by precipitation in methanol. The yield was 70%, the HT value was 82%, the PDI was 2.1, the number average molecular weight Mn was 8.7KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 11%, that is, the copolymerization degree was 11mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L4 are shown as follows:
[0068]
[0069] Among them, x=11mmol%, y=89mmol%.
[0070] Example 5
[0071] This embodiment provides an ester-thiophene-hexylthiophene copolymer L5, and the synthesis method thereof is as follows:
[0072] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.1mmol), 2-bromo-3-hexylthiophene (0.4mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L5 was obtained by precipitation in methanol. The yield was 53%, the HT value was 89%, the PDI was 2.0, the number average molecular weight Mn was 7.4KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 16%, that is, the copolymerization degree was 16mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L5 are as follows:
[0073]
[0074] Among them, x=16mmol%, y=84mmol%.
[0075] Example 6
[0076] This embodiment provides an ester-thiophene-hexylthiophene copolymer L6, and the synthesis method thereof is as follows:
[0077] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.125mmol), 2-bromo-3-hexylthiophene (0.375mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L6 was obtained by precipitation in methanol. The yield was 55%, the HT value was 83%, the PDI was 1.3, the number average molecular weight Mn was 4.7KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 20%, that is, the copolymerization degree was 20mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L6 are shown as follows:
[0078]
[0079] Among them, x=20mmol%, y=80mmol%.
[0080] Example 7
[0081] This embodiment provides an ester-thiophene-hexylthiophene copolymer L7, and the synthesis method thereof is as follows:
[0082] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.015mmol), 2-bromo-3-hexylthiophene (0.485mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L7 was obtained by precipitation in methanol. The yield was 71%, the HT value was 87%, the PDI was 2.5, the number average molecular weight Mn was 13.5KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 2.5%, that is, the copolymerization degree was 2.5mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L7 are shown as follows:
[0083]
[0084] Among them, x=2.5mmol%, y=97.5mmol%.
[0085] Example 8
[0086] This embodiment provides an ester-thiophene-hexylthiophene copolymer L8, and the synthesis method thereof is as follows:
[0087] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.025mmol), 2-bromo-3-hexylthiophene (0.475mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L8 was obtained by precipitation in methanol. The yield was 68%, the HT value was 86%, the PDI was 2.2, the number average molecular weight Mn was 12.1KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 4.8%, that is, the copolymerization degree was 4.8mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L8 are shown as follows:
[0088]
[0089] Among them, x=4.8mmol%, y=95.2mmol%.
[0090] Example 9
[0091] This embodiment provides an ester-thiophene-hexylthiophene copolymer L9, and the synthesis method thereof is as follows:
[0092] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.05mmol), 2-bromo-3-hexylthiophene (0.45mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L9 was obtained by precipitation in methanol. The yield was 66%, the HT value was 90%, the PDI was 2.3, the number average molecular weight Mn was 9.8KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 9.3%, that is, the copolymerization degree was 9.3mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L9 are shown as follows:
[0093]
[0094] Among them, x=9.3mmol%, y=90.7mmol%.
[0095] Example 10
[0096] This embodiment provides an ester-thiophene-hexylthiophene copolymer L10, and the synthesis method thereof is as follows:
[0097] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.075mmol), 2-bromo-3-hexylthiophene (0.425mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L10 was obtained by precipitation in methanol. The yield was 59%, the HT value was 89%, the PDI was 2.1, the number average molecular weight Mn was 7.5KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 13.9%, that is, the copolymerization degree was 13.9mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L10 are shown as follows:
[0098]
[0099] Among them, x=13.9mmol%, y=86.1mmol%.
[0100] Embodiment 11
[0101] This embodiment provides an ester-thiophene-hexylthiophene copolymer L11, and the synthesis method thereof is as follows:
[0102] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.1mmol), 2-bromo-3-hexylthiophene (0.4mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester-based thiophene-hexylthiophene copolymer L11 was obtained by precipitation in methanol. The yield was 63%, the HT value was 86%, the PDI was 2.0, the number average molecular weight Mn was 8.8KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester-based thiophene-hexylthiophene copolymer segment was 18.9%, that is, the copolymerization degree was 18.9mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester-based thiophene-hexylthiophene copolymer L11 are shown as follows:
[0103]
[0104] Among them, x=18.9mmol%, y=81.1mmol%.
[0105] Example 12
[0106] This embodiment provides an ester-thiophene-hexylthiophene copolymer L12, and the synthesis method thereof is as follows:
[0107] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.125mmol), 2-bromo-3-hexylthiophene (0.375mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L12 was obtained by precipitation in methanol. The yield was 77%, the HT value was 84%, the PDI was 1.7, the number average molecular weight Mn was 7.9KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 22.7%, that is, the copolymerization degree was 22.7mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L12 are shown as follows:
[0108]
[0109] Among them, x=22.7mmol%, y=77.3mmol%.
[0110] Embodiment 13
[0111] This embodiment provides an ester-thiophene-hexylthiophene copolymer L13, and the synthesis method thereof is as follows:
[0112] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxymethyl)thiophene (0.06mmol), 2-bromo-3-hexylthiophene (0.44mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L13 was obtained by precipitation in methanol. The yield was 69%, the HT value was 83%, the PDI was 2.0, the number average molecular weight Mn was 7.8KDa, and the molar percentage of 3-(2-acetoxymethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 10%, that is, the copolymerization degree was 10mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L13 are as follows:
[0113]
[0114] Among them, x=10mmol%, y=90mmol%.
[0115] Embodiment 14
[0116] This embodiment provides an ester-thiophene-hexylthiophene copolymer L14, and the synthesis method thereof is as follows:
[0117] Under nitrogen atmosphere, 2-bromo-3-(2-acetoxyethyl)thiophene (0.06mmol), 2-bromo-3-hexylthiophene (0.44mmol), potassium carbonate (0.75mmol), dipyridine carboxaldehyde palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), dimethylacetamide (4mL) were reacted at 100°C for 24h, and ester thiophene-hexylthiophene copolymer L14 was obtained by precipitation in methanol. The yield was 70%, the HT value was 88%, the PDI was 2.1, the number average molecular weight Mn was 10.0KDa, and the molar percentage of 3-(2-acetoxyethyl)thiophene segment in the ester thiophene-hexylthiophene copolymer segment was 10%, that is, the copolymerization degree was 10mmol; the structures of the dipyridine carboxaldehyde palladium catalyst C1 and the ester thiophene-hexylthiophene copolymer L14 are shown as follows:
[0118]
[0119] Among them, x=10mmol%, y=90mmol%.
[0120] Embodiment 15
[0121] This embodiment provides a pin-type perovskite solar cell, the specific cell structure is ITO / ester-thiophene-hexylthiophene copolymer / perovskite active layer / PCBM / BCP / Ag, and the specific implementation steps are as follows:
[0122] (1) Cleaning of the transparent substrate layer: First, take out the ITO transparent conductive glass, tear off the plastic protective film on the surface, and first use detergent to gently wipe the surface oil and dirt, and then ultrasonically clean it in a 0.2wt% detergent aqueous solution, deionized water, and isopropanol for 15 minutes respectively. Finally, use nitrogen to blow dry the isopropanol on the ITO surface and put it in a box for later use.
[0123] (2) Deposition of hole transport layer: The ester-thiophene-hexylthiophene copolymer of Example 1 was prepared into a precursor solution of 0.2 mg / mL, and the solvent was chlorobenzene. The cleaned ITO was first placed in an ultraviolet ozone cleaner for surface hydrophilic treatment, and then the precursor solution was sucked out with a pipette and evenly covered on the ITO surface. The solvent was dried by spin coating (500 rpm / min, 3s; 3000 rpm / min, 20s).
[0124] (3) Preparation of wetting layer: The purchased aluminum oxide nanoparticle (<50 nm) dispersion (20%) was mixed with isopropanol at a volume ratio of 1:50 (aluminum oxide dispersion: isopropanol) to prepare an aluminum oxide precursor solution. The prepared aluminum oxide precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole transport layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).
[0125] (4) Preparation of perovskite active layer: The FAPbI3 system perovskite precursor solution (1000 rpm / min, 3s; 5000 rpm / min, 30s, 100 μL chlorobenzene was added as anti-solvent at 21s) was aspirated with a pipette and evenly covered on the surface of the wetting layer to form a perovskite active layer, and then annealed on a hot stage at 100°C for 30-60 min.
[0126] (5) Deposition of electron transport layer: Weigh 20 mg of PCBM and add 1 mL of chlorobenzene to prepare the precursor solution of the electron transport layer. The electron transport layer precursor solution was deposited on the surface of the perovskite active layer by spin coating (500 rpm / min, 3 s; 2500 rpm / min, 20 s).
[0127] (6) Deposition of hole blocking layer: 8 mg of BCP was weighed and 16 mL of isopropanol was added to prepare a precursor solution. The prepared precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole blocking layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).
[0128] (7) Deposition of metal electrode layer: A 100 nm thick Ag film was thermally evaporated under high vacuum at an evaporation rate of 0.3 Å / s for 20 nm and then deposited on the surface of the hole blocking layer at 1 Å / s to a thickness of 100 nm.
[0129] Example 16
[0130] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-based thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-based thiophene-hexylthiophene copolymer of Embodiment 2" to obtain the pin-type perovskite solar cell of Embodiment 16.
[0131] Embodiment 17
[0132] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-based thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-based thiophene-hexylthiophene copolymer of Embodiment 3" to obtain the pin-type perovskite solar cell of Embodiment 17.
[0133] Embodiment 18
[0134] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 4" to obtain the pin-type perovskite solar cell of Embodiment 18.
[0135] Embodiment 19
[0136] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-based thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-based thiophene-hexylthiophene copolymer of Embodiment 5" to obtain the pin-type perovskite solar cell of Embodiment 19.
[0137] Embodiment 20
[0138] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-based thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-based thiophene-hexylthiophene copolymer of Embodiment 6" to obtain the pin-type perovskite solar cell of Embodiment 20.
[0139] Embodiment 21
[0140] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 7" to obtain the pin-type perovskite solar cell of Embodiment 21.
[0141] Embodiment 22
[0142] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 8" to obtain the pin-type perovskite solar cell of Embodiment 22.
[0143] Embodiment 23
[0144] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 9" to obtain the pin-type perovskite solar cell of Embodiment 23.
[0145] Embodiment 24
[0146] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 10" to obtain the pin-type perovskite solar cell of Embodiment 24.
[0147] Embodiment 25
[0148] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 11" to obtain the pin-type perovskite solar cell of Embodiment 23.
[0149] Embodiment 26
[0150] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 12", thereby obtaining the pin-type perovskite solar cell of Embodiment 24.
[0151] Embodiment 27
[0152] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 13", thereby obtaining the pin-type perovskite solar cell of Embodiment 27.
[0153] Embodiment 28
[0154] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 15 in that the "ester-thiophene-hexylthiophene copolymer of Embodiment 1" in step (2) of Embodiment 15 is replaced with "ester-thiophene-hexylthiophene copolymer of Embodiment 14", thereby obtaining the pin-type perovskite solar cell of Embodiment 28.
[0155] The performance of the pin-type perovskite solar cells of Examples 15 to 28 was tested. The test method is as follows and the results are shown in Table 1.
[0156] (1) JV characteristic curve: The JV characteristic curve of the device was measured using a Keithley 2440 light source under a simulated AM1.5G spectrum.
[0157] The light intensity was calibrated using a solar simulator (Newport, 91160) from NREL using a standard silicon solar cell device. The effective measurement area was 0.07 cm 2 , under reverse and forward bias scans, the scan rate was 100mV / s and the bias range was from -0.2V to 1.2V.
[0158] Table 1. Performance of perovskite solar cells of Examples 15 to 28.
[0159] sample Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Embodiment 15 1.08 21.23 68.92 15.80 Example 16 1.09 21.97 69.03 16.53 Embodiment 17 1.07 21.45 69.14 15.87 Embodiment 18 1.06 22.31 71.08 16.81 Embodiment 19 1.07 22.68 71.11 17.26 Embodiment 20 1.10 22.50 70.99 17.57 Embodiment 21 1.09 21.82 71.07 16.90 Embodiment 22 1.07 21.94 71.13 16.70 Embodiment 23 1.08 22.06 71.16 16.95 Embodiment 24 1.10 22.19 72.25 17.64 Embodiment 25 1.06 22.21 72.31 17.02 Embodiment 26 1.11 22.34 72.60 18.00 Embodiment 27 0.92 22.06 63.24 12.83 Embodiment 28 0.90 21.85 62.96 12.38
[0160] As can be seen from Table 1, the ester-thiophene-hexylthiophene copolymers prepared in Examples 15 to 28 of the present invention have high Voc and high FF for preparing perovskite solar cells, thereby obtaining a high PCE value.
[0161] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An ester-thiophene-hexylthiophene copolymer, characterized in that: The ester-thiophene-hexylthiophene copolymer is a copolymer of 3-hexylthiophene and ester-thiophene, wherein the ester-thiophene is selected from at least one of 3-(2-acetoxyethyl)thiophene and 3-(2-acetoxymethyl)thiophene, wherein the molar percentage of the ester-thiophene segment in the ester-thiophene-hexylthiophene copolymer segment is 2.9% to 9% or 16% to 20%; the number average molecular weight of the ester-thiophene-hexylthiophene copolymer is 4.7 to 13.8 KDa.
2. The esterthiophene-hexylthiophene copolymer according to claim 1, characterized in that: The esterthiophene-hexylthiophene copolymer is a random copolymer.
3. The esterthiophene-hexylthiophene copolymer according to claim 1, characterized in that: The structure of the ester thiophene-hexyl thiophene copolymer is shown in formula (I) or formula (II): Formula (I) Formula (II) The molar percentage of the ester-thiophene chain segment in the ester-thiophene-hexylthiophene copolymer chain segment is 2.9% to 9% or 16% to 20%; the number average molecular weight of the ester-thiophene-hexylthiophene copolymer is 4.7 to 13.8 KDa.
4. The esterthiophene-hexylthiophene copolymer according to claim 1, characterized in that: The HT value of the esterthiophene-hexylthiophene copolymer is ≥80%, and the PDI is ≤2.
5.
5. A method for preparing an esterthiophene-hexylthiophene copolymer, characterized in that: The steps include: Under the catalysis of pyridine carboxaldehyde palladium catalyst, the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene react to obtain the ester thiophene-hexylthiophene copolymer according to any one of claims 1 to 4; The bromine-substituted ester-based thiophene is selected from at least one of 2-bromo-3-(2-acetoxyethyl)thiophene and 2-bromo-3-(2-acetoxymethyl)thiophene.
6. The method for preparing the esterthiophene-hexylthiophene copolymer according to claim 5, characterized in that: The pyridine carboxaldehyde palladium catalyst is selected from a dipyridine carboxaldehyde palladium catalyst, and the structure of the dipyridine carboxaldehyde palladium catalyst is shown below: ; and / or, the molar ratio of the bromine-substituted ester thiophene to 2-bromo-3-hexylthiophene is 3-25:75-97; and / or, the ratio of the total mole of the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene to the mole of the palladium catalyst is 1:0.001-0.01; And / or, the reaction further contains an inorganic base, an organic acid and a solvent; And / or, the reaction temperature is 80-120° C. and the reaction time is 12-36 hours.
7. The method for preparing the esterthiophene-hexylthiophene copolymer according to claim 6, characterized in that: The inorganic base includes at least one of potassium carbonate and sodium carbonate; And / or, the organic acid includes at least one of pivalic acid and caproic acid; and / or, the solvent comprises N,N-dimethylacetamide; and / or, the ratio of the total mole of the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene to the mole of the inorganic base is 1-1.5:1-1.5; And / or, the ratio of the total mole of the bromine-substituted ester thiophene and 2-bromo-3-hexylthiophene to the mole of the organic acid is 2.5-4.5:
1.
8. Use of the ester-thiophene-hexylthiophene copolymer prepared by the preparation method of the ester-thiophene-hexylthiophene copolymer according to any one of claims 1 to 4 or the ester-thiophene-hexylthiophene copolymer according to any one of claims 5 to 7 in the preparation of perovskite solar cells.
Citation Information
Patent Citations
Polythiophene based active layer for solar cells
US20120279569A1